STRATEGI OPERASIONAL PEMBANGKIT LISTRIK TENAGA AIR (PLTA) DEPARTMENT MAINTENANCE & UTILITIES PT. VALE INDONESIA - Fahmi Fahmi; Muhammad Ali; Jusni Jusni (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
To face challenges, a company must prepare a good operational strategy and formulate the right, effective and efficient priority strategy that must be done by management. This study aims to analyze the internal factors that become the strengths and weaknesses in the determination of priority strategies, external factors that become strengths and weaknesses in the determination of priority strategy, and priority strategy that best suits the needs of the department Utilities operation of hydro plant in achieving Goal by optimizing the existing resource using SWOT and AHP analysis. This research was conducted at PT. Vale Indonesia Tbk. Department of Maintenance and Utilities on Utilities operation of hydro plant. Data collection was done by combining in-depth interview method, observation (observation) and document review, and questionnaire. Based on the results of AHP calculation of internal environmental factor analysis into strengths and weaknesses in the determination of priority strategy on the Operation of hydro plant shows the employee's commitment to the operation of hydro plant to work in accordance with the vision and mission of the hydro plant operational into the highest strength with a weight of 0.423. For Saturation with work routine is a weakness of the Department Utilities of Hydro plant with the highest weight of 0.426. Based on the results of AHP calculations on the analysis of external environmental factors Development of potential and competence of individual employees has the highest weight of 0.418. While the shift caused by shift is the biggest threat factor with the weight of 0.415. Based on the results of AHP calculations on the determination of operational strategies in improving the performance of the Operation of hydro plant in a sequence that provides career certainty consistently and periodically in accordance with the results of competence test of each employee, publicize the achievements and performance of the employees operation of hydro plant to cross department Thereby enhancing employee confidence and loyalty, providing 24-hour healthcare facilities in work areas and sports facilities, rotating personnel shifts of hydro plant operational staff, providing local communities the opportunity to attend training schools prepared by the company prior to recruitment of new employees.